Pengaruh Penambahan NPK dan UREA Pada Media Air Pemeliharaan Terhadap Pertumbuhan Rumput Laut Caulerpa racemosa var. uvifera - Setiaji, Kristama; Santosa, Gunawan Widi; Sunaryo, Sunaryo (977-2407769)
Seaweed is a low-level photosynthetic organism that has no stem, leaves, or root. Seaweeds are commonly used as food and as an ingredient for the food industry, pharmaceutical industry, cosmetics industry, and other industries. Caulerpa is potential to be cultivated because it has been known and liked by people. Beside, Caulerpa also has economic value for people. This kind of seaweed grows seasonally, but sometimes Caulerpa cannot be found in the water even during the season because its growth highly depends on the environment’s condition. This situation leads to Caulerpa production shortages. Hence, Caulerpa cultivation is necessary. The purpose of this research is to know the effect of adding NPK and urea at different concentration to the growth rate of Caulerpa racemosa var. uvifera. This research was conducted from May till July 2011 at Laboratory of Marine Science, Faculty of Fisheries and Marine Science Diponegoro University, Teluk Awur, Jepara. C. racemosa var. uvifera samples were taken from Bandengan coastal waters, Jepara the method used in this research was experimental method with a completely randomized block design. This research used 5 of treatments, each repeated 3 times. The cultivation medium used was sea water that has been deposited for 24 hours, with fertilizers added in different concentration: medium A was not added with fertilizers, medium B was added with 1.60 ppm of NPK fertilizers and 5.40 ppm of urea fertilizers, medium C was added with 4.93 ppm of NPK fertilizers and 10.82 ppm of urea fertilizers, medium D was added with 8.26 ppm of NPK fertilizers and 16.26 ppm of urea fertilizers, and medium E was added with 11.60 ppm of NPK fertilizers and 21.70 ppm of urea fertilizers. The data gained were wet weight of seaweed and water quality of the cultivation medium. The data was analyzed using ANOVA. The result showed that the addition of NPK and urea fertilizers in different concentration gave different effect (p < 0.01) among each treatment. The highest specific growth rate of C. racemosa var. uvifera was achieved in medium D (6.86 % per day with 8.26 ppm of NPK and 16,26 ppm of urea addition) while the lowest specific growth rate was obtained in medium A (5.97% per day with no NPK and urea addition).